The introduction of the brown hare to Britain and its bio-cultural impact: zooarchaeological and morphometric approaches - Fowler, Thomas (2020)
The introduction of new fauna is almost without exception not solely about enriching human diet. Instead, non-native fauna can be linked with the arrival new cultural phenomena, especially in the realm of religion. The religious and secular festival of Easter provides a case study with which to explore this phenomenon in the British archaeological and historical record, as its three associated animals - the brown hare, European rabbit, and chicken - are all not native to Britain.